2015
DOI: 10.1080/19942060.2015.1004787
|View full text |Cite
|
Sign up to set email alerts
|

Development of new “multivolute casing” geometries for radial force reduction in centrifugal pumps

Abstract: Large radial force causes several issues in pumps, such as noise, vibration, and extra load on the bearings. To reduce the radial force, the effects of concentric volute and multivolute geometry on the head, efficiency, and radial force of a low speed centrifugal pump at off-design conditions were investigated. Commercial software with the k -ω turbulence model and automatic near wall treatment was employed for the prediction of fluid flow inside the pump. Flow simulations for three casings concentric at 180°,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…The turbulence model applied was the Shear Stress Transport (SST). This model is very accurate for the numerical investigation of flow within a centrifugal pump (Shojaeerd et al, 2012), also used by other authors, including Akemi et al (2015) and Li et al (2018) The fluid domain is a rotary domain with constant rotational speed of 1500 rpm. Therefore, all boundary rotated with this speed, except the inlet, which was stationary.…”
Section: Methodsmentioning
confidence: 99%
“…The turbulence model applied was the Shear Stress Transport (SST). This model is very accurate for the numerical investigation of flow within a centrifugal pump (Shojaeerd et al, 2012), also used by other authors, including Akemi et al (2015) and Li et al (2018) The fluid domain is a rotary domain with constant rotational speed of 1500 rpm. Therefore, all boundary rotated with this speed, except the inlet, which was stationary.…”
Section: Methodsmentioning
confidence: 99%
“…Numerical flow modeling of pumps addressing problems and working conditions of real hydraulic machinery became an established method of analysis in recent years. [32][33][34][35][36][37] In this study, the calculation domain includes impeller, volute, suction and discharge pipes, front sidewall gap and front wear ring clearance, without balancing holes. A high-quality structured mesh was developed for the geometry consisting of more than 2.5 million nodes (see Figure 2).…”
Section: Numerical Simulationmentioning
confidence: 99%
“…The results showed that the maximum amplitudes of pressure fluctuations in volute at serious cavitation condition are twice that at noncavitation condition because of the violent disturbances caused by cavitation shedding and explosion. Hamed [5] investigated reducing the radial force, the effects of concentric volute, and multivolute geometry on the head, efficiency, and radial force of a low speed centrifugal pump at off-design conditions. The results showed that the triple-volute is the most appropriate volute geometry at off-design conditions.…”
Section: Introductionmentioning
confidence: 99%